2014
DOI: 10.2399/tahd.14.35220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polypharmacy and complementary therapy use in patients >=65 years, attending to Family Medicine Outpatient Clinic of Şişli Etfal Training and Research Hospital

Abstract: ÖzetAmaç: Kronik hastal›klar›n prevalans›n›n artmas› nedeniyle yafll› bireyler günümüzde daha fazla say›da ilaç kullanmaktad›r. Çal›flmam›-z›n amac› poliklini¤imize baflvuran 65 yafl ve üzeri hastalarda polifarmasi ve tamamlay›c› tedavi kullan›m s›kl›¤› ve bunlar›n sosyodemografik özelliklerle iliflkisini de¤erlendirmektir.Yöntem: Tan›mlay›c› özellikteki bu çal›flmaya, Eylül-Ekim 2012 tarihlerinde fiiflli Etfal E¤itim ve Araflt›rma Hastanesi Aile Hekimli¤i polikliniklerine baflvuran 65 yafl ve üzeri hastalar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(17 reference statements)
0
4
1
1
Order By: Relevance
“…Önal et al reported the frequency of using 5 or more drugs as 36.5%, Şayir et al found that 69% of the participants used 4 or more drugs. 24,25 Although the frequency of polypharmacy was found to be different in our study and other samples, the striking thing is that the rate is very high. As the number of drugs that were being used by the patients in our study increased, their inappropriate drug use rates also increased significantly.…”
Section: Discussioncontrasting
confidence: 76%
“…Önal et al reported the frequency of using 5 or more drugs as 36.5%, Şayir et al found that 69% of the participants used 4 or more drugs. 24,25 Although the frequency of polypharmacy was found to be different in our study and other samples, the striking thing is that the rate is very high. As the number of drugs that were being used by the patients in our study increased, their inappropriate drug use rates also increased significantly.…”
Section: Discussioncontrasting
confidence: 76%
“…Ülkemizde de huzurevlerinde ve sağlık hizmeti veren birimlerde yapılan benzer çalışmalar kronik hastalıklar ve çoklu ilaç kullanımının yaşlı hastalar için önemli bir sorun olduğunu ortaya koymaktadır (10)(11)(12) . Arslanve ark.…”
Section: Discussionunclassified
“…Despite the aforementioned advantages, the use of CAM methods may have disadvantages 17. Chronic illnesses whose prevalence increases with age, multiple drug use, and decreased functional capacity may increase the possibility of encountering side effects attributable to CAM use 18.…”
Section: Introductionmentioning
confidence: 99%
“…16 Despite the aforementioned advantages, the use of CAM methods may have disadvantages. 17 Chronic illnesses whose prevalence increases with age, multiple drug use, and decreased functional capacity may increase the possibility of encountering side effects attributable to CAM use. 18 Misuse of CAM methods, cessation of prescribed drugs when using CAMs, and the interaction of these methods with drugs are among the risk factors that may lead to health issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation